HADIS MENJILATI JARI SETELAH MAKAN PERSPEKTIF MA’AN AL-HADITH - Riri Rizqiyatul Falah; Hartati Hartati; Lukman Zain MS (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2019)
Differences editorial in a hadith theme are possible, one of which is in the tradition licking fingers after eating. In the theme of the hadith there are 2 very prominent editors, namely in the form of a sentence kalimat ÙŠÙŽÙ„Ù’Ø¹ÙŽÙ‚ÙŽÙ‡ÙŽØ§ Ø§ÙŽÙˆÙ’ ÙŠÙÙ„Ù’Ø¹ÙÙ‚ÙŽÙ‡ÙŽØ§or only use the word ÙŠÙŽÙ„Ù’Ø¹ÙŽÙ‚ÙŽÙ‡ÙŽØ§ both of them are fi'il mud}a>riâ€™. But there is also the Hadith use the word mad Ù„ÙŽØ¹ÙÙ‚ÙŽ which is fi'il madi. The word ÙŠÙÙ„Ù’Ø¹ÙÙ‚ÙŽÙ‡ÙŽØ§ in the matan editor means 'licking fingers to others'. At first glance maybe the message of the Prophet Muhammad. in the hadith strongly recommends licking your fingers after eating, but whether to ask for help from others to do so. This paper aims to find out the analysis of maâ€™an al-hadith with an effort to trace the meaning of licking fingers after eating.